The memory thieves : a conjuror novel - Clayton, Dhonielle (Clayton, Dhonielle. Conjureverse, 2023)
In her second year at Arcanum Training Institute, Ella grapples with fame, unearths a perilous school secret, and faces a mysterious magical illness outbreak, prompting her, alongside Brigit and Jason, to clear her name, while working tirelessly to safeguard the Marvellian realm from impending chaos.